Effect of Individual Supportive Psychotherapy on Stress in Family Members of Surgical Intensive Care Unit Patients - จอมโคกสูง จุรานุช; แนบเกษร ชนัดดา; ชัยเสนา ดาลลาส จิณห์จุฑา (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this quasi-experimental study was to examine the effect of individual Supportive psychotherapy on stress in family members of surgical intensive care unit patients. The sample included twenty family members of crisis patients from surgical intensive care unit patients in Ramathibodi hospital who met the inclusion criteria. The participants were randomly assigned into the experimental and control group, 10 for each group. The experimental group received individual supportive psychotherapy for 5 sessions within 5 days and each session took about 60 to 90 minutes. Whereas those in the control group received only routine nursing care. The stress in family members of crisis patients questionnaire was used to collect data at pretest and posttest. Descriptive statistics, independent t-test and pair t-test were employed for data analysis. Study results revealed that experimental group had significantly lower mean scores of stress at posttest than that of control group (p < .001). In experimental group, there was significantly lower mean score of stress at posttest than pretest (p < .001). From the results, it showed that the individual supportive psychotherapy could reduce stress among family members of surgical intensive care unit patients. Therefore, nurses and related health personnel could apply this individual supportive psychotherapy in order to reduce stress among family members of crisis patients in other intensive care unit patients.